Reconstruction of bilateral inferomedial gluteal defects after resection of hidradenitis suppurativa with symmetrical keystone flaps designed parallel to relaxed skin-tension lines: A case report. Issue 14 (April 2020) - Kim, Hyo Bong; Lim, Soo Yeon; Yoon, Chi Sun; Kim, Kyu Nam
Abstract: Rationale: Surgical treatment of hidradenitis suppurativa (HS) is challenging. Wide excision of affected lesions followed by skin graft or flap coverage has been recommended to achieve remission and prevent recurrence. Herein, we present our experience of bilateral inferomedial gluteal defects coverage using symmetrical keystone flaps (KFs) designed parallel to relaxed skin-tension lines (RSTLs). Patient concerns: An 18-year-old man was admitted for chronic inflammatory lesions in both inferomedial gluteal areas. Diagnoses: Physical examination revealed multiple sinuses with broad surrounding scars in both inferomedial gluteal areas, which led to a diagnosis of HS. Interventions: We performed wide excision on all affected lesions. The size of the final defects was 6 × 10 cm on the right side, and 5 × 9 cm on the left side. We covered the defects with KFs 9 × 15 cm (right) and 8 × 12 cm (left), which were based on the hotspots of the interior gluteal artery and internal pudendal artery perforators, and parallel to RSTLs. Outcomes: The flaps were inset without tension on each side, and the donor sites were closed primarily. All flaps fully survived and there were no postoperative complications. The patient was satisfied with the final outcome after 6 months of follow-up. Lessons: Successful reconstruction of bilateral inferomedial gluteal defects was achieved after resection of HS using symmetrical KFs designed parallel to RSTLs. The KF technique considering RSTLs could be a good reconstructive option for gluteal HS.